Work motivation as a bridges for leadership, workspace, and performance - Sumarmi, Saptaningsih; Saputra, Elvan; Elhariry, Basma; Musa, Hussein Gibreel; Samsudin, Samsudin (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2025)
Optimal employee performance can create positive impacts, such as increased productivity, better work quality, and more efficient target achievement. This study investigates how transformational leadership and physical work environment affect employee performance in Indonesia’s public sector, with work motivation as a mediator. Using a quantitative approach, data were collected from all 244 employees of Daerah Istimewa Yogyakarta Department of Manpower and Transmigration and analyzed via SEM-PLS. Results reveal that transformational leadership directly improves employee performance and indirectly through work motivation. While the physical work environment does not directly impact performance, it significantly enhances motivation, which in turn boosts performance. These findings underscore that psychological factors (motivation) play a more critical role than physical workspace conditions in driving performance. The study highlights the dominance of transformational leadership and motivational mechanisms over environmental factors in public sector settings. Practically, organizations should prioritize leadership development and motivational strategies rather than focusing solely on physical workspace improvements. By integrating internal (motivation) and external (leadership, environment) factors, this research provides novel insights into performance dynamics in government institutions, challenging traditional assumptions about the direct impact of physical work conditions. The findings contribute to a deeper understanding of how public sector performance can be enhanced through leadership and psychological empowerment